Wells Abbey
Vaulting similarly gained from these advances. The weight was reduced by fitting thin panels between a net of load-supporting ribs. The intersections gave another opportunity for decorative work. Often gilded and painted, they too contributed to a richness which in the early part of the century reached another high water mark of the medieval world.